Physiotherapeutic approach in women undergoing hysterectomy - Martins, Edgar Manoel; Girola, Carolina; Wolpe, Raquel Eleine; Roza, Thuane Huyer Da; Honório, Gesilani Júlia Da Silva (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Hysterectomy is the second most frequently performed surgery on the female genital tract. The patients submitted to this procedure are susceptible to complications that can be avoided by preventive measures, among them, the accomplishment of physiotherapy. This study aims to verify in the scientific literature the physiotherapeutic approaches in women submitted to hysterectomy. Systematic Researches of indexed articles were carried out in databases: Pubmed, LILACS, MEDLINE, PEDro e SciELO, between the years 2009 and 2019. 9 articles fit the inclusion and exclusion criteria determined to compose this systematic review. The main topics of physiotherapeutic activity found in the articles were: techniques for strengthening the pelvic floor musculature, breathing exercises, aerobic exercises and strengthening of the core, upper and lower extremities, transcutaneous electrical stimulation, evaluation of physical performance, fatigue, pain and quality of life, besides applying alternative techniques such as: acupuncture, electroacupuncture, auricular electrical stimulation, transcutaneous electrical stimulation, electric acustimulation and acupressure. There is a great diversity of studies showing beneficial effects in the different interventions developed, serving as a basis to direct the physiotherapeutic conducts in hysterectomy approaches, aiming at complementary resources for the best care of the patient undergoing this procedure. Keywords: Hysterectomy. Physical Therapy Modalities. Physical Therapy Specialty.